Breast cancer survivors' preferences for social support features in technology-supported physical activity interventions: findings from a mixed methods evaluation. Issue 2 (16th November 2018) - Lloyd, Gillian R; Hoffman, Sara A; Welch, Whitney A; Blanch-Hartigan, Danielle; Gavin, Kara L; Cottrell, Alison; Cadmus-Bertram, Lisa; Spring, Bonnie; Penedo, Frank; Courneya, Kerry S; Phillips, Siobhan M
Abstract: Incorporating peer and professional social support features into remotely delivered, technology-supported physical activity interventions may increase their effectiveness. However, very little is known about survivors' preferences for potential social features. This study explored breast cancer survivors' preferences for both traditional (e.g., coaching calls and peer support) and innovative (i.e., message boards and competitions) social support features within remotely delivered, technology-supported physical activity interventions. Survivors [ N = 96; M age = 55.8 ( SD = 10.2)] self-reported demographic and disease characteristics and physical activity. A subset ( n = 28) completed semistructured phone interviews. Transcribed interviews were evaluated using a thematic content analysis approach and consensus review. Following interviews, the full sample self-reported preferences for social features for remotely delivered physical activity interventions via online questionnaires. Questionnaire data were analyzed using descriptive statistics. Four themes emerged from interview data: (a) technology increases social connectedness; (b) interest in professional involvement/support; (c) connecting with similar survivors; and (d) apprehension regarding competitive social features. Quantitative data indicated that most survivors were interested in social features including a coach (77.1 per cent), team (66.7 per cent), and exercise buddy (57.3 per cent). Survivors endorsed sharing their activity data with their team (80.0 per cent) and buddy (76.6 per cent), but opinions were mixed regarding a progress board ranking their activity in relation to other participants' progress. Survivors were interested in using a message board to share strategies to increase activity (74.5 per cent) and motivational comments (73.4 per cent). Social features are of overall interest to breast cancer survivors, yet preferences for specific social support features varied. Engaging survivors in developing and implementing remotely delivered, technology-supported social features may enhance their effectiveness. Abstract : Breast cancer survivors believed that remotely delivered (mobile application, online website, or phone) social support features would help them increase their physical activity, yet preferences for specific social features varied.